Review on Some Bangladeshi Medicinal Plants with Anticancer Properties - Ashrafi, Sania; Masud, Mohammad Mehedi (Dhaka University Journal of Pharmaceutical Sciences, 2022)
According to WHO, cancer is one of the leading causes of death worldwide, accounting for an estimated 9.6 million deaths in 2018. More significant improvements have been made in the management and treatment of cancer, still there remains scope for the betterment of treatment procedures. Mostsynthetic anticancer drugs are known to develop resistance, show cytotoxicity against normal cells due to their non-selective nature, and cause tremendous side effects. Medicinal plants are significantly feasible sources of organic compounds, for their better availability, cheaper price, fewer side effects, and sometimes better therapeutic efficacy, which may benefit the world commercially or act as an important starting point for identifying lead compounds to develop modified derivatives. This article describes the ethnobotanical properties of 15 available medicinal plants of Bangladesh having anti-cancer properties. Dhaka Univ. J. Pharm. Sci. 21(1): 95-104, 2022 (June)